Education, social justice and the legacy of Deakin University reflections of the Deakin diaspora - Tinning, Richard; Tinning, Richard; Sirna, Karen (Transgressions: cultural studies and education, 2011)
The late Joe Kincheloe once wrote that {u2018}... the amazing Deakin Mafia provided innovative and unprecedented critical scholarship on education for a few short yearsu2019. Informed by various theoretical perspectives (eg., critical theory, neo-Marxist, poststructuralist, postcolonial, feminist, critical literacy, Bourdieuian, Foucauldian) key Deakin University scholars pursued their commitments to social justice though education. A certain criticality characterised their work. Individually and collectively they created a national and international reputation for critical scholarship in education. Since that time (the 1980s and 90s), however, most of the Deakin u2018mafiau2019 have moved to senior academic posts elsewhere in Australian and internationally and their influence in educational research and discourse now continues as members of the u2018Deakin diasporau2019. This collection is an account of the stories of many of these scholars. It will provide valuable reading for any scholar of education who is particularly interested in critical pedagogy and the critical project in education more generally. It also provides insights into what makes a faculty of education successful at a particular point in time.